PENGEMBANGAN JIWA WIRAUSAHA UMKM MELALUI INKUBATOR BISNIS STIE BIMA PADA EVENT MOTOGP MANDALIKA - Puji Muniarty; Wulandari; M Syukur Dwiriansyah; Ovriyadin (Jurnal Abdi Insani, 2023)
Bima High School of Economics (STIE) is one of the higher education institutions that focuses on developing entrepreneurship on the island of Sumbawa, NTB. As a program that becomes a space for entrepreneurs to grow, the STIE Bima business incubator made a real breakthrough by participating in the MotoGP event which will be held in 2022. The purpose of the activity is to introduce products created by the creativity of the Bima UMKM academic community so that its marketing network is wider and to develop the potential of the soul. entrepreneurship for MSME actors/academicians as well as collaboration opportunities for entrepreneurs so they can contribute to benefit others. This activity was carried out using a participatory method which involved the active role of the STIE Bima academic community along with several MSMEs located around the Bima City and Regency area. Activities carried out in several stages, namely preparation, implementation, monitoring and evaluation. Activity results: The MotoGP event is not only a means of motorbike racing activities and tourism promotion, but also the development of MSMEs so that they go public so as to create a multiplier effect. Of course, the ultimate goal is public welfare considering that MSMEs are a means of employment that drives the creative economy. This phenomenon has encouraged STIE Bima as an entrepreneurship campus in Bima City to actively encourage the development of MSMEs by involving and participating in activities related to entrepreneurship. In addition, buyers are satisfied with the form of service and a friendly welcome when buying products at prices that buyers can afford. Conclusion: The output of this activity can also be accessed in several Bima local media, including on kahaba.net, www.gardaasakota.com, and STIE Bima's official Instagram. The promotion of MSME products on MotorGp shows that UMKM products in the Bima area can compete in the modern market.